Երիտասարդաց քրիստոնեական ընկերակցության գործունեությունը Օսմանյան կայսրությունում (1881-1909 թթ.) - Վ. Համբարձումյան (ՀՀ ԳԱԱ հրատ.)
The Young Men’s Christian Association (YMCA) was founded in 1844. Already after a decade it was widely spread in Western European countries and North America, becoming the largest youth movement in the world. Христианская Ассоциация молодых людей (YMCA) была основана в 1844 году. Спустя десять лет она была широко известна в Западной Европе и Северной Америке, став одной из самых крупных молодёжных организаций в мире.
Keywords: History; Modern History; D History